Desain dan Realisasi Sistem Komunikasi Cahaya Tampak untuk Streaming Teks berbasis PWM - Trio Adiono; Syifaul Fuada; Angga Pradana (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2017)
The design and implementation of visible light communication systems for transmitting digital data (texts) have been discussed in this paper. Then, two evaluations were performed also, i.e. the demonstration of streaming text through the visible light as a proof-of-concept system design. The next evaluation is a BER measurement intended to know the VLC system performance quantitatively. The value of BER against the several parameters: by the variation of distance and its reception angle. The proposed VLC system works well until the photodiode reception angle to the LEDs up to 50°. According to evaluation, our system can operate optimally within 30 – 80 cm or 50 – 130 cm of optical channel range depending on the Gain setting option. To support the reliability of noise from ambient light and interference lamps such as fluorescent lamps, the filters circuit are employed: high pass filter and DC-offset remover. Based on the BER analysis, the filters can compensate the problem of ambient light noise (DC-offset signal) and interference lamp (100-150 Hz of carrier frequency). The speed of data-rate obtained with 1-PWM modulation and the low-cost analog component is 3.3 kbps.